2015
DOI: 10.1016/j.canlet.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

RYBP predicts survival of patients with non-small cell lung cancer and regulates tumor cell growth and the response to chemotherapy

Abstract: Ring1 and YY1 binding protein (RYBP) is a member of Polycomb group (PcG) proteins and regulates cell growth through both PcG-dependent and -independent mechanisms. Our initial study indicated that RYBP is down-regulated in human non-small cell lung cancer (NSCLC) tissues. The present study determined the molecular role of RYBP in the development of NSCLC. We systemically investigated the association between the RYBP expression and the survival of patients with NSCLC. We also carried out in vitro and in vivo st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 31 publications
3
27
0
Order By: Relevance
“…More recently, a growing body of evidence has demonstrated aberrant expression, chromosomal translocation, or missense mutation of multiple PcG members in a variety of cancers, suggesting an implication of the PcG deregulation in the cancer development . For example, Ring1 and YY1 binding protein (RYBP), a new member of the PcG family, has been found downregulated in hepatocellular and non–small cell lung cancers and enforced RYBP expression suppressed proliferation, induced apoptosis, and increased chemosensitivity of these cancer cells . These findings indicated the tumor‐suppressive effect of RYBP on cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a growing body of evidence has demonstrated aberrant expression, chromosomal translocation, or missense mutation of multiple PcG members in a variety of cancers, suggesting an implication of the PcG deregulation in the cancer development . For example, Ring1 and YY1 binding protein (RYBP), a new member of the PcG family, has been found downregulated in hepatocellular and non–small cell lung cancers and enforced RYBP expression suppressed proliferation, induced apoptosis, and increased chemosensitivity of these cancer cells . These findings indicated the tumor‐suppressive effect of RYBP on cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…In the in vivo studies, the tumor tissue samples were homogenized in NP-40 lysis buffer and the supernatants were collected. The proteins from cell and tissue lysates were quantified, and the protein samples were then subjected to Western blotting analysis for the expression levels of MDM2, p53, and p21 using the methods described previously [39, 40]. …”
Section: Methodsmentioning
confidence: 99%
“…Tumor and tissue sections with a thickness of 5 µm were deparaffinized in xylenes, rehydrated, and washed with PBS. For the immunohistochemistry studies [39, 40], the tumor slides were incubated with a biotinylated antihuman MDM2 antibody (diluted 1:50 in 5% BSA in PBS) for 1 h at room temperature. For TUNEL staining [39, 40], tissue sections were incubated with proteinase K (20 µg/mL in 10 mM Tris-HCl, pH 7.4) for 15 min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Deregulation of PcG proteins disrupts this balance and often contributes to cell transformation and neoplasticity [48,49]. As mentioned previously, RYBP is a multifaceted adaptor involved in both the PcG complex and apoptosis; indeed, several studies have demonstrated dysregulated expression of RYBP in various human tumour tissues, including prostate, lung, liver, breast and cervical cancers, as well as Hodgkin's lymphoma (HL), and glioblastoma multiforme [43,[50][51][52][53][54][55][56][57]. Here, we will discuss the function of RYBP in these different types of cancer.…”
Section: The Roles Of Rybp In the Cancermentioning
confidence: 99%